Legal Policy Addition of The Minimum Age Limit for Marriage in Law Number 16 of 2019 and Relevance With Efforts to Press the Application for Marriage Dispensation - Achmad Bagus Syaifullah; M. Fauzan Zenrif; Burhanuddin Susamto (Al-Fikru: Jurnal Ilmiah, 2023)
This study aims to analyze the addition of the minimum age limit for marriage in law No. 16 of 2019 and its relevance to efforts to suppress requests for marital dispensation. This study used the library research method with a statutory and conceptual approach. The results of the study show that the formulation of changes to the minimum age limit for marriage in Law Number 16 of 2019 has implemented efforts to prevent early marriage. If viewed from the perspective of hikmatut tasyri', it contains an affirmation that the change represents the maintenance of maqashid sharia. Efforts to increase the minimum age limit for marriage are closely related to the impact of the surge in marriage dispensations received by the religious courts. The marriage dispensation actually applies to legal subjects who do not meet the minimum age criteria and if this minimum age limit is changed to a higher one, the relevance of the dispensation application will also increase. It can be seen that efforts to prevent early marriage are realized in the implementation of the minimum age limit, but the agenda of minimizing dispensation is the responsibility of justice enforcers, namely the panel of judges. Considerations given in the marriage dispensation judicial process are expected to prioritize physical, mental, sociological, and economic conditions.